Review Probabilitas Menemukan Elektron dengan Fungsi Gelombang Simetri dan Antisimetri pada Molekul - Yusron, Moh.; Firdausi, K. Sofjan; Sumariyah, Sumariyah (BERKALA FISIKA, 2007)
The probability density of  and  for the symmetry and asymmetry wave function respectively, for  ion has been simulated. The  and  wave function have been obtained through the solutions of one dimensional time-independent Schrödinger equation.  The  and  are formed then by linear combination of individual solution of wave function of hydrogen atom. The probability density is calculated and simulated for several values of inter nuclear distance in Bohr radius, using Matlab 6.5. The interpretation of  shows that the probability in finding the electron in the space between inter nuclear distance of 0,2 is very small for asymmetry and very large for symmetry wave function. If the inter nuclear distance is made larger in several , the probability becomes smaller. The probability density is just equal to individual in finding electron in a hydrogen atom. Key words: The probability density, symmetry and asymmetry wave function, the  ion.